Phytochemical, Antioxidant, Cytotoxic, Antibacterial Activity, and Enzymatic Inhibition Study of Piper Betle Leaves - Al-Gburi, Ahmed Saad; Khalid Mustafa, Kareem; Ullah, Saeed; Khan, Ajmal; Qayum, Usama; Al Touby, Salem Said; Manickam, Balamurugan; Rehman, Najeeb Ur; Al-Harrasi, Ahmed; Weli, Afaf Mohammed (Iranian Journal of Pharmaceutical Sciences, 2024)
The Piper betle plant, known for its pharmacological properties, has been traditionally used in Asian cultures. The objective of the current study is to assess the antioxidant, cytotoxic, antibacterial, and enzymatic inhibitions of leaf extracts of the P. betle. DPPH radicals were used to assess the antioxidant potential. The Lethality Assay for Brine Shrimp was used to assess the cytotoxic potential of plant extracts. The disc diffusion method was used to measure the leaves' antibacterial activity against various Gram stains. The inhibitory potential of four enzymes linked to different diseases was screened spectrophotometrically. Chromatographic procedures were used to isolate active substances, and their structures were determined using spectroscopic approaches. The results indicated that the P. betle leaves extracts to possess potent antioxidant activity, highest with the EAPB (ethylacetate, P. betle) followed by DCPB (dichloromethane, P. betle), HPB (n-hexane, P. betle), BPB (n-butanol, P. betle) and AQPB (aqueous P. betle). For cytotoxic activity, the EAPB has the most potent cytotoxic activity among the tested extracts. AQBP and HPB showed activity against all bacteria used, while (EAPB and DCPB displayed good activities against all organisms except Streptococcus aglaciate. For anti-diabetic activity, DCPB, and EAPB both showed high percent inhibition and low IC50. The identified compound, allylpyrocatechol, isolated from the EAPB fraction of betel leaf attributed higher inhibitory activity than the standard against α-glucosidase with an IC50 of 42.61 ± 1.27. For anti-ulcer activity, the DCPB had the highest urease % inhibition and the lowest IC50 value, while (BPB) and AQBP fractions had lower levels of inhibition and higher IC50 values. DCPB and EAPB exhibited neurodegenerative therapeutic potential by targeting prolyl endopeptidase with good activity having IC50 values of 26.82 ± 0.36 and 52.92 ± 21.30 µg/mL). Furthermore, these extracts were tested for their therapeutic potential for skin diseases by targeting the tyrosinase enzyme. Interestingly, HPB and DCPB displayed good inhibitory capability with IC50 values of 36.14 ± 0.72, and 44.72 ± 1.28 µg/mL, respectively, compared to the standard kojic acid (IC50 = 7.49 ± 0.21 µg/mL). In conclusion, crude extracts of Piper betle leaves exhibit potent antioxidant, antibacterial, and moderately cytotoxic effects. It also has strong anti-ulcer and anti-diabetic properties. Additionally, it exhibits strong anti-pigentation properties and good neurodegenerative potential.